PEMBELAJARAN FISIKA MATERI GERAK LURUS MELALUI MODEL POE (PREDICT-OBSERVE-EXPLAIN) DISERTAI DIAGRAM VEE DI KELAS X SMA NEGERI PAKUSARI - Elinda Septy Kusuma Wardani; Yushardi Yushardi; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2017)
This article reported the result of an experimental research about the effect of POE (Predict-Observe-Explain) with Vee diagram on the straight motion learning at tenth grade SMA Negeri Pakusari in 2016/2017 academic year. The objectives of this research were to describe the learning activities during POE learning model with Vee diagram and to know the effect of POE learning model with Vee diagram to the cognitive learning outcomes in straight motion learning. The design of this research was post test only control group design. The data of the learning activities was collected by using observation and portfolio. Based on the data, the average of the learning activities was 71,37% which means active. The data of the cognitive learning outcomes in straight motion was collected by using post test. Then, the data collected was analyzed by using independent sample t-test (SPSS 20). The difference of the achievement between experiment class and control class is done by obtained significant value of 0.012. It means the result of this research proved that the use of POE learning model with Vee diagram significantly affected the cognitive learning outcomes at tenth grade SMA Negeri Pakusari. Keywords: POE (Predict-Observe-Explain) learning model, Vee diagram, cognitive learning outcomes , learning activities